Promoting Collaboration in Jabodetabekjur: A Learning Regions Perspective on Knowledge-Based Economy - Muhammad Rahmat Yananda; Irfan Ridwan Maksum; Heri Fathurahman (Policy & Governance Review, 2017)
This research raised issues on knowledge – based economy (KBE) in Jabodetabekjur, especially Bogor, Depok and South Tangerang. Using qualitative approach, this research examines collaboration involving city governments, college/research institutions, businesses/industries,communities and found the reasons why collaborations for the beneft of KBE in Jabodetabekjur as a learning region has not established yet. The causes are: (1) lack of cohesion in terms of policy/administration, ecology, economics and social system; (2) institutional failure; (3) non optimalregional cooperation; (4) unalignment with the national urban development strategies; and (5) loss of momentum in KBE development. Learning regions can be constructed by analyzing a path or trajectories combined with the potentials of the urban region elements (Academicians, Businesses, Communities and Governments). They can also be constructed via governance approach and development of appropriate organizational models. City’s administrations should take active roles as the initiator of the collaboration process opted by certain types and activities. Strategy and policy – making related to collaboration gave rise to: (1) KBE development themes; (2) vision/ mission statements; and (3) principles of engagement and capacities. Resources gaps were found and can be applied as inputs to build joint projects, namely: (1) incubation and innovation centers; and (2) product innovation promotion center.